2005
DOI: 10.1007/s00464-004-8826-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic revisional bariatric surgery: myths and facts

Abstract: Laparoscopic revisional bariatric surgery is safe and effective. However, it should be performed only by experienced bariatric and laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…RYGB on the other hand appears to have adequate EWL, decreasing to 32 kg/m 2 from 45 kg/m 2 at 12 months in one study [17]. Furthermore, complication rates are similar to rebanding rates [11,14,17,[20][21][22]24]. When revisional surgery is performed by experienced hands, creation of an LRYGB after failed AGB can have similar complication rates as primary LRYGB surgery [8,14,17,19,21,24,25].…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…RYGB on the other hand appears to have adequate EWL, decreasing to 32 kg/m 2 from 45 kg/m 2 at 12 months in one study [17]. Furthermore, complication rates are similar to rebanding rates [11,14,17,[20][21][22]24]. When revisional surgery is performed by experienced hands, creation of an LRYGB after failed AGB can have similar complication rates as primary LRYGB surgery [8,14,17,19,21,24,25].…”
Section: Discussionsupporting
confidence: 50%
“…Nonetheless, in the setting of inadequate weight loss after band placement, RYGB appears to be a superior procedure [8,14,17,19,21,24,25]. Of four studies analyzing the results after rebanding only one reported postoperative BMI, and it was unchanged after 12 months [11,14,20,22].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations